PENERAPAN METODE VIKOR DALAM PENILAIAN KINERJA TENAGA PENDIDIK - Leonard Tambunan; Novidawaty Tambunan; Muhammad Iqbal; Juwita Azizah (JSR : Jaringan Sistem Informasi Robotik, 2022)
The assessment system for educators is a system used to assess the performance of the best educators. In general, the performance assessment of educators is carried out annually with the aim of improving and improving their performance. The results of this performance become a decision-making tool such as promotion, dismissal, transfer, intensive giving or providing feedback for the educators. However, the number of educators who will be selected is the driving force for assessing the performance of the educators, because it is expected that an automation process uses technology to launch these educators. The purpose of this study was to apply the VIKOR method in assessing the performance of educators. The method used is the VIKOR method, the basic concept of VIKOR is to find the weighted sum of the performance appraisals for each alternative on all attributes. The VIKOR method can help decision making to shape values into the best alternative. The assessment in the research that has been carried out using 4 (four) assessments are: Pedagogic, Personality, Social and Professional with criteria for each competency using the VIKOR method. In this study, testing was carried out on 10 data for educators.